Peran Aplikasi Subsidi Tepat MyPertamina dalam Peningkatan Akurasi dan Efektivitas Pencatatan Penjualan - Nazwa Nurani Putri (Universitas Muhammadiyah Metro, 2026)
The 3 kg LPG cylinder subsidy is a government policy to help low-income communities and micro-businesses meet their energy needs. The Targeted Subsidy Program is supported by the MyPertamina application as a medium for digital transaction recording to ensure more targeted distribution. This study aims to examine the use of this application in improving the accuracy of 3 kg LPG sales records at PT Gaharu Digdaya Bahari. The method used is descriptive qualitative through observation, interviews, and documentation. The results of the study show that the application is able to improve the accuracy of recording, transparency of distribution, and internal control, although there are still obstacles in terms of internet network and user ability in operating the application.